Early determination of the reproductive potential of beef heifers using reproductive tract scoring, pelvimetry and transrectal ultrasonography - Thompson, P.N. (Peter N.) (University of Pretoria, 2014)
Thesis (PhD)--University of Pretoria, 2013.